Digital Marketing Strategies for Household Processed Food MSMEs via Social Media and E-Commerce in Karawang - Saptaji Saptaji; Mimin Aminah; Rizal Syarief (Electronic Journal of Education, Social Economics and Technology, 2025)
The rapid development of information and communication technology has transformed the way businesses operate, especially among Micro, Small, and Medium Enterprises (MSMEs). As of July 2024, the Ministry of Cooperatives and MSMEs reported that 25.5 million MSMEs, or 38.93% of Indonesia’s total 65.5 million MSMEs, have integrated into the digital ecosystem. One of the most dynamic sectors is the processed food household industry, including those in Karawang Regency. According to the Karawang Cooperative and MSME Office, the number of processed food MSMEs reached 15,538 units in 2022, an increase of 23.69% from the previous year. However, challenges remain, particularly in limited digital marketing adoption and suboptimal technology utilization. Data from the Karawang Industry and Trade Office (2025) show that 78% of MSMEs use social media for marketing and 30% use e-commerce, yet 7% reported no increase in sales, while 65% experienced varied revenue growth. This study aims to formulate digital marketing strategies to enhance the sales performance of processed food MSMEs in Karawang Regency. Primary data were collected through interviews and questionnaires with selected MSME actors, while secondary data were sourced from government institutions and literature studies. The analysis employed descriptive methods, IFE–EFE, IE, SWOT, and Analytical Hierarchy Process (AHP). The results show that the top priority strategy is the Integrated Digital Branding and Sales Program, followed by collaborative digital capacity building, digital quality assurance and product differentiation, and community based digital promotion for cost efficiency and local competitiveness.